The mutiny on board HMS bounty - Bligh, William, 1827-1901 ([Boston, Mass] : Thomson Heile, 2007)
Captain William Bligh recounts his experiences in 1789 when his ship'Bounty' was taken over in a mutiny and he and a crew of eighteen men were set adrift in an open boat in the southern Pacific Ocean
Title from container
Keywords: Bligh, William, -- 1754-1817; Travel in literature -- History; Bounty Mutiny, 1789 -- Juvenile literature; Survival; Oceania -- Description and travel -- Early works to 1800 -- Juvenile literature